2015
DOI: 10.15380/2277-5706.jcsr.15.025
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation therapy – comparison of efficacy of three different protocols

Abstract: Background: To study the efficacy of vitamin D supplementation therapy with three different protocols. Methods:In protocols 1 (intensive) and 3 (standard) oral cholecalciferol was given 60,000 IU/week/8 weeks followed bimonthly for 12 weeks. In protocol 2 parenteral-bolus cholecalciferol was given as 600,000 IU loading dose, 8 weeks later followed by cholecalciferol 60,000IU bimonthly for 12 weeks. Elemental calcium (1 g/day) was administered for full duration of study in all three protocols. Serum albumin, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…There is no consensus on the amount of vitamin D supplement required nor the route of administration. The previous studies[ 13 23 ] attest to the advantages of this approach, as such doses were better able to sustain normal (>20 ng/mL) serum levels of 25(OH) vitamin D. A comparison of three different protocols of vitamin D administration in vitamin D-deficient Indian women[ 24 ] concluded that the most effective regimen was the one that employed a high parenteral dose at the beginning followed by oral doses. In the WHI (Womens’ Health Initiative) study, the majority of subjects were already on calcium and vitamin D supplements and additional supplements did not protect against fractures.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on the amount of vitamin D supplement required nor the route of administration. The previous studies[ 13 23 ] attest to the advantages of this approach, as such doses were better able to sustain normal (>20 ng/mL) serum levels of 25(OH) vitamin D. A comparison of three different protocols of vitamin D administration in vitamin D-deficient Indian women[ 24 ] concluded that the most effective regimen was the one that employed a high parenteral dose at the beginning followed by oral doses. In the WHI (Womens’ Health Initiative) study, the majority of subjects were already on calcium and vitamin D supplements and additional supplements did not protect against fractures.…”
Section: Discussionmentioning
confidence: 99%